Recruitment of Honorary Teachers in Public Elementary Schools - Gde Dharma Putrawan; Sri Marmoah; Supianto (Jurnal Ilmiah Sekolah Dasar, 2024)
The teacher is one of the factors that determine the success of education. Honorary teachers are a reality in Indonesia's education sector, including in public elementary schools. This research explores the meaning related to the recruitment of honorary teachers in public elementary schools. The research adopts a qualitative approach with a phenomenological method. The data in this study are transcripts of in-depth interviews with informants. Fourteen informants in this study comprised twelve honorary elementary school teachers and two school principals. There are three stages of data analysis data reduction, data presentation, and drawing conclusions. This research found that public elementary school s employ honorary teachers to address teacher shortages. Each honorary teacher has their own reasons for registering as an honorary teacher, such as job opportunities, bringing happiness to their parents, and a sense of dedication. Public elementary schools can recruit honorary teachers even if they do not have a PGSD degree. The implications of this research are related to meeting the needs of teachers in public elementary schools, increasing the welfare of honorary teachers, and teacher recruitment that takes into account the suitability of educational qualifications.